Analisis Pengelolaan Pajak Parkir Terhadap Pendapatan Asli Daerah pada Badan Pengelola Pajak dan Retribusi Daerah Kota Medan - Putri Aulia Br Siregar; Nurlaila Nurlaila (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Parking tax is one of the local revenue and should be potential enough to affect the increase in local revenue, one of which is the original income in the city of Medan. This is because every year many people use private transportation and not only that, buildings or malls that provide parking spaces are also increasing. With the development of existing facilities, for example, more and more entertainment venues are opened, resulting in an increase in parking taxes every year. Based on this explanation, the purpose of this study is to find out how parking tax management is on Medan City's Original Regional Revenue. By doing this analysis, we become aware of how the management is carried out by the government to increase local revenue. Management itself basically includes four aspects, namely planning, organizing, implementing, supervising/controlling. In this study, the author uses a qualitative research method using a descriptive qualitative approach. For the data collection method in this study, namely by conducting interviews with City BPPRD employees and also utilizing documentaries, and on-site observations.